Application of prophylactic or pre-emptive therapy after allogeneic transplantation for high-risk patients with t(8;21) acute myeloid leukemia. Issue 1 (31st December 2023) - Guo, Wenwen; Liu, Xin; Wang, Mingyang; Liu, Jia; Cao, Yigeng; Zheng, Yawei; Zhai, Weihua; Chen, Xin; Zhang, Rongli; Ma, Qiaoling; Yang, Donglin; Wei, Jialin; et al.
ABSTRACT : Objectives: To determine the impact of pretransplant measurable residual disease (pre-MRD) and the efficacy of maintenance therapy in t(8;21) acute myeloid leukemia (AML) patients after allogeneic hematopoietic cell transplantation (allo-HCT). Methods: We retrospectively analyzed 100 t(8;21) AML patients who underwent allo-HCT between 2013 and 2022. 40 patients received pre-emptive therapy including immunosuppressant adjustment, azacitidine, and donor lymphocyte infusion (DLI) combined with chemotherapy. 23 patients received prophylactic therapy, including azacitidine or chidamide. Results: Patients with a positive pre-MRD (pre-MRDpos) had a higher 3-year cumulative incidence of relapse (CIR) (25.90% [95% CI, 13.87%–39.70%] vs 5.00% [95% CI, 0.88%–15.01%]; P = 0.008). Pre-MRDpos patients were less likely to have a superior 3-year disease-free survival (DFS) (40.83% [95% CI, 20.80%–80.16%]) if their MRD was still positive at 28 days after transplantation (post-MRD28 pos). The 3-year DFS and CIR were 53.17% (95% CI, 38.31% – 73.80%) and 34.87% (95% CI, 18.84% – 51.44%), respectively, for patients receiving pre-emptive interventions after molecular relapse. The 3-year DFS and CIR were 90.00% (95%CI, 77.77% – 100%) and 5.00% (95%CI, 0.31% – 21.10%), respectively, for high-risk patients receiving prophylactic therapy. In most patients, epigenetic-drug-induced adverse events were reversible with dose adjustment or temporary discontinuation. Conclusion: Patients with pre-MRDpos and post-MRD28 pos were more likely to have higher rates of relapse and inferior DFS, even after receiving pre-emptive interventions. Prophylactic therapy may be a better option for high-risk t(8;21) AML patients; however, this warrants further investigation.